Effect of Calcium Compounds Obtained from Fish Processing By-Product on Calcium Metabolism in Rats - Phatchareerat Tongchan (Prince of Songkla University, 2016)
Thesis (M.Sc., Food Science and Technology)--Prince of Songkla University, 2011